Biocultural approaches to well-being and sustainability indicators across scales. Issue 12 (December 2017) - Sterling, Eleanor; Filardi, Christopher; Toomey, Anne; Sigouin, Amanda; Betley, Erin; Gazit, Nadav; Newell, Jennifer; Albert, Simon; Alvira, Diana; Bergamini, Nadia; Blair, Mary; Boseto, David; et al.
Abstract Monitoring and evaluation are central to ensuring that innovative, multi-scale, and interdisciplinary approaches to sustainability are effective. The development of relevant indicators for local sustainable management outcomes, and the ability to link these to broader national and international policy targets, are key challenges for resource managers, policymakers, and scientists. Sets of indicators that capture both ecological and social-cultural factors, and the feedbacks between them, can underpin cross-scale linkages that help bridge local and global scale initiatives to increase resilience of both humans and ecosystems. Here we argue that biocultural approaches, in combination with methods for synthesizing across evidence from multiple sources, are critical to developing metrics that facilitate linkages across scales and dimensions. Biocultural approaches explicitly start with and build on local cultural perspectives — encompassing values, knowledges, and needs — and recognize feedbacks between ecosystems and human well-being. Adoption of these approaches can encourage exchange between local and global actors, and facilitate identification of crucial problems and solutions that are missing from many regional and international framings of sustainability. Resource managers, scientists, and policymakers need to be thoughtful about not only what kinds of indicators are measured, but also how indicators are designed, implemented, measured, and ultimately combined to evaluate resource use and well-being. We conclude by providing suggestions for translating between local and global indicator efforts. Biocultural approaches combining local values, knowledge, and needs with global ecological factors provide a fruitful indicator framework for assessing local and global well-being and sustainability, and help bridge the divide between them.